PENERBITAN SERTIFIKAT HAK MILIK ATAS TANAH SEHUBUNGAN DENGAN PERATURAN DAERAH KOTA DENPASAR NOMOR 6 TAHUN 2005 TENTANG RETRIBUSI IZIN PERUNTUKAN PENGUNAAN TANAH - Prawira Buwana, Dewa Gede; Agung, I Gusti Nyoman; Darmada, I Nyoman (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 01, Februari 2014)
In this time almost on every joint streets in Denpasar city shown advertisement: “sold the plot of land”, or “sold the plot of land ready to build”. Terminology plot of land is popular progressively in society, and many society require the land area for their residences and buy the land area which have in plot the land by right owner of land or by investors. The plot of land gives definition that a land area can by some or size measure as according to buyer with a certain rights reasons. Generally a land area can be divided or fragmented to coherent rights which designate that the land is represent the land by destining live house in settlement area. According to Regulation of Government number 24 year 1977, certificate is a rightful authority document which used as an evidence tool to right of land, right of management, property right of house and right of insurance which had booked on each their certificate. Every individual who have the right of land which representing law subject is entitled to do deed of law of their land, like to waive their right to the new right receiver candidate, and it’s legal. Seeing much the plot of land area in Denpasar City, Denpasar city governmental in order to arranged development of settlement and housing with environment vision, which including in arrange about allotment and exploiting of land have published Decision of Denpasar Mayor Number 396 year 2000 31 July 2000 about execution plot of land in Denpasar city and Regulation of Denpasar city number 6 year 2005 specified on 22 December year 2005, about Retribution Permit Allotment Usage of Land. This regulation basically also arrange about licensing which must fulfill by individual and also law department conducting plot of land in Denpasar city. The method which used in this research is empiric method. Empiric method is a research about a problem which happened from its reality or practice.
Keywords: Certificate, Plot of Land, License, Law Consequence